2004
DOI: 10.1136/hrt.2003.015057
|View full text |Cite
|
Sign up to set email alerts
|

One year comparison of costs of coronary surgery versus percutaneous coronary intervention in the stent or surgery trial

Abstract: Objectives: To compare initial and one year costs of coronary artery bypass grafting (CABG) versus percutaneous coronary intervention (PCI) in the stent or surgery trial. Design: Prospective, unblinded, randomised trial. Setting: Multicentre study. Patients: 988 patients with multivessel disease. Interventions: CABG and stent assisted PCI. Main outcome measures: Initial hospitalisation and one year follow up costs. Results: At one year mortality was 2.5% in the PCI arm and 0.8% in the CABG arm (p = 0.05). Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 28 publications
1
29
3
Order By: Relevance
“…Considering the group of patients for each procedure, the hospitalization costs of Group 1 were 12.3% greater than those of Group 2, thereby corroborating with other published works. However, the percentage increase in respect to CABG of the present sample, is less than the increases reported by Favarato et al (35.9%) [10], in the ARTS study (65.4%) [9] and Weintraub et al (88.5%) [24].…”
Section: Resultscontrasting
confidence: 55%
“…Considering the group of patients for each procedure, the hospitalization costs of Group 1 were 12.3% greater than those of Group 2, thereby corroborating with other published works. However, the percentage increase in respect to CABG of the present sample, is less than the increases reported by Favarato et al (35.9%) [10], in the ARTS study (65.4%) [9] and Weintraub et al (88.5%) [24].…”
Section: Resultscontrasting
confidence: 55%
“…2,[11][12][13] Patients were recruited from 53 study centers in 11 European countries and Canada between November 5, 1996, and December 12, 1999. Patients with multivessel coronary artery disease were considered for inclusion and enrolled if the consensus view of the trial surgeon and interventionist was that revascularization was clinically indicated and appropriate by either strategy.…”
Section: Methodsmentioning
confidence: 99%
“…7,9,15,28,[35][36][37][38][39] However, most of these studies are limited by relatively short follow-up durations 7,34,36,39 or Costs and QALYs are discounted at 3% per year. Δ indicates difference between CABG and PCI groups; CABG, coronary artery bypass grafting; CI, confidence interval; ICER, incremental cost-effectiveness ratio for coronary artery bypass grafting versus percutaneous coronary intervention; LM, left main; PCI, percutaneous coronary intervention; QALY, quality-adjusted life-year gained; and SYNTAX, Synergy Between Percutaneous Coronary Intervention With TAXUS and Cardiac Surgery.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%